Histopathological and Immunophenotypical Analysis of Canine Mucinous Rectal Adenocarcinoma - Damasceno, Karine Araújo; Rabelo, Bruna Salgado; Gamba, Conrado de Oliveira; Souza, Cristina Maria de; Campos, Liliane Cunha; Campos , Cecília Bonolo de; Ferreira , Enio; Cassali, Geovanni Dantas (Brazilian Journal of Veterinary Pathology, 2012)
Rectal adenocarcinomas are uncommon in dogs and usually present poor prognosis. The present work describes the morphological and immunophenotypical findings of a rectal mucinous adenocarcinoma in a bitch. Histological analysis revealed a malignant epithelial proliferation in a tubulopapillary pattern forming multiple intratubular cell layers. Moderate amount of PAS-positive amorphous eosinophilic content within neoplastic tubules and extruded into the stroma was observed. Immunohistochemical analysis revealed neoplastic cells considered positive for cytokeratin, Her-2, COX-2 and E-caderin and with low p53 expression. A high proliferation index was observed. Based on histological and immunophenotypical findings, the diagnosis of mucinous adenocarcinoma was established.